MENYEMAI PENDIDIKAN KARAKTER DI MADRASAH; TELAAH ATAS FUNGSIONALISASI MADRASAH DALAM PENGUATAN KARAKTER PESETA DIDIK - Mohammad Makinuddin (JP : JURNAL PENDIDIKAN, 2018)
The paper is outlining the relationship and position of the madrasah in strengthening the education of characters, begins with a description of the school, and educational character, and concludes with an explanation of the madrasa and educational character. The conclusions of this paper are; First, the Madrasah as a sub- system National education is also involved in the strengthening of character education in Indonesia. So give the contribution potential in producing men who love to God and the universe and its contents, entirely responsible, disciplined and independent, honest, respectful and polite, love affection, care, and employment together, trust yourself, creative, work hard and abstinence surrender, justice and leadership, good and low heart, and tolerance, love peace and unity. Second, Madrasah had a concern that is highly and seriousness in doing strengthening educational character. Forming human beingswho can be trusted, have a sense of respect and atten-tion, care, understand the spirit of citizenship, particularly a sincere, courageous, diligence and integrity. Third, character education in madrasas can be seen from various aspects including; aspects of the curriculum objectives and charac-teristics madrasas, competency formulations, material characteristics and graduate competencies.Keyword: Madrasah, Character Education